Leydig tumor in normal sized ovaries causing clitoromegaly: A case report - Thomas F Chavez; Minita Singh; Vaidehi Avadhani; Regina Leonis (Elsevier, 2024)
We describe an unusual presentation of a rare Leydig tumor presenting in bilateral ovaries that are otherwise normal in size for postmenopausal women. A 66-year-old woman presented with postmenopausal bleeding and during her work-up acutely developed clitoromegaly. Her diagnostic work-up revealed a 1.8 cm left ovarian complex cyst and extremely elevated testosterone levels. Management included hysterectomy and bilateral salpingo-oophorectomy. Final pathology revealed Leydig tumors in the bilateral ovaries. This case discusses a rare presentation of a rare tumor and highlights the importance of a thorough examination of the female genitalia and investigation for root cause.